Grimace scale assessment during Citrobacter rodentium inflammation and colitis development in laboratory mice - Peppermüller, Pia Pascale; Gehring, Jonathan; Zentrich, Eva; Bleich, André; Häger, Christine; Buettner, Manuela (Frontiers in Veterinary Science, 2023)
Bacterial infections and chronic intestinal inflammations triggered by genetic susceptibility, environment or an imbalance in the intestinal microbiome are usually long-lasting and painful diseases in which the development and maintenance of these various intestinal inflammations is not yet fully understood, research is still needed. This still requires the use of animal models and is subject to the refinement principle of the 3Rs, to minimize suffering or pain perceived by the animals. With regard to this, the present study aimed at the recognition of pain using the mouse grimace scale (MGS) during chronic intestinal colitis due to dextran sodium sulfate (DSS) treatment or after infection with Citrobacter rodentium. In this study 56 animals were included which were divided into 2 experimental groups: 1. chronic intestinal inflammation (n=9) and 2. acute intestinal inflammation (with (n=23) and without (n=24) C. rodentium infection). Before the induction of intestinal inflammation in one of the animal models, mice underwent an abdominal surgery and the live MGS from the cage side and a clinical score were assessed before (bsl) and after 2, 4, 6, 8, 24 and 48 hours. The highest clinical score as well as the highest live MGS was detected 2 hours after surgery and almost no sign of pain or severity were detected after 24 and 48 hours. Eight weeks after abdominal surgery B6-Il4/Il10-/- mice were treated with DSS to trigger chronic intestinal colitis. During the acute phase as well as the chronic phase of the experiment, the live MGS and a clinical score were evaluated. The clinical score increased after DSS administration due to weight loss of the animals but no change of the live MGS was observed. In the second C57BL/6J mouse model, after infection with C. rodentium the clinical score increased but again, no increased score values in the live MGS was detectable. In conclusion, the live MGS detected post-operative pain, but indicated no pain during DSS-induced colitis or C. rodentium infection. In contrast, clinical scoring and here especially the weight loss revealed a decreased wellbeing due to surgery and intestinal inflammation.